Epigenetic regulation of ageing: linking environmental inputs to genomic stability - Benayoun, Bérénice A. (Nat Rev Mol Cell Biol, 2015)
Ageing is affected by both genetic and non-genetic factors. Here, we review the chromatin-based epigenetic changes that occur during ageing, the role of chromatin modifiers in modulating lifespan and the importance of epigenetic signatures as biomarkers of ageing. We also discuss how epigenome remodeling by environmental stimuli impacts several aspects of transcription and genomic stability, with important consequences on longevity, and outline epigenetic differences between the ‘mortal soma’ and the ‘immortal germline’. Finally, we discuss the inheritance of ageing characteristics and potential chromatin-based strategies to delay or reverse hallmarks of ageing or age-related diseases.